Impact of Collaborative Intervention Programme on Pre-Primary and Primary School Teachers’ Awareness, Acquisition and Utilisation of Educational Research Findings in Oyo State, Nigeria (2014)
Research plays a significant role in the implementation of educational programmes and effective discharge of teaching responsibilities. However, studies show that Nigerian teachers do not utilise research information in the choice of effective teaching strategies, lesson planning, instructional material design and evaluation of pupils’ learning. This has led to inadequate expert knowledge necessary for improving pupils’ learning outcomes, hence, there is need for the development of communication network and links between researchers and classroom teachers. However, there is a dearth of empirical studies on the utilisation of educational research findings in Nigeria. This study, therefore, determined the impact of collaborative intervention programme on pre-primary and primary school teachers’ awareness, acquisition and utilisation of educational research findings in Oyo State, Nigeria. The study adopted one-group pretest-posttest preexperimental design. Sixty teachers of pre-primary (30) and primary (30) schools were purposively selected from Oyo South Senatorial District. Seven instruments were used: Educational Research Findings Package for Collaborative Intervention (r = 0.86), Teachers’ Awareness of Educational Research Findings Questionnaire (r = 0.82), Teachers’ Acquisition of Research Findings Questionnaire (r = 0.84), Teachers’ Utilization of Research Findings Questionnaire (r = 0.83), Teachers’ Classroom Observation Scale (r = 0.73), Teachers’ Interview Guide and Focus Group Discussion Guide. Six sessions of Focus Group Discussion with teachers and six micro-teaching as well as a seminar were also used. The study lasted for twelve weeks. Five research questions were answered and four hypotheses tested at .05 level of significance. Data were analysed using descriptive statistics, paired t-test, independent samples’ t-test and content analysis. Teachers’ level of awareness (pretest = 71.9%; posttest = 87.4%), acquisition (pretest = 63.8%; posttest = 68.5%), and utilisation (pretest = 81.5%; posttest = 88.3%) improved after the collaborative intervention. Their classroom practices reflected more educational research findings (65.2%) than the situation before intervention (45.8%). There were significant differences in the teachers’ level of awareness (t = 4.22; df = 59; p < .05) and utilisation of research (t = 2.38; df = 59; p < .05) before and after intervention in favour of the post-intervention measures. There was no significant difference between teachers’ acquisition of research before and after intervention. Interviews revealed that teachers earlier relied on sources of knowledge which are not research-based but after intervention, they requested for the dissemination of research findings directly from researchers. Reasons for non-utilisation of research findings by the teachers include lack of proper understanding and skills for implementation of research findings. The collaborative intervention programme impacted positively on the pre-primary and primary school teachers’ awareness, acquisition and utilisation of educational research findings. Therefore, researchers need to adopt the collaborative approach for disseminating research findings. Research institutions should design and popularise research dissemination channels based on collaboration. Funding agencies should sponsor educational researchers in the organisation of seminars and workshops for disseminating new research findings.